Organic and inorganic selenium supplementation on the productive and reproductive performance of hair ewes - Díaz-García, Luis H. (2019)
The objective of this study was to evaluate the effect of supplementation with organic and inorganic selenium on the productive and reproductive performance of ewes and their offspring. Selenium (Se) is an essential mineral for sheep, studies have found its intestinal absorption and biodisponibility in the animal is greater when it comes from an organic source. A total of 18 multiparous and 22 nulliparous ewes Pelibuey breed were used in this study, averaging 54.8 ± 9.4 kg and 39.7 ± 5.6 kg of body weight (BW). The experimental units were blocked by the number of parturitions (none or more than one). Then randomly assigned to one treatment: basal diet +1.2 ppm of organic Se (OSe, Sel-Plex®) or basal diet +1.2 ppm inorganic Se (ISe). Using the linear model PROC MIXED, BW changes were measured in ewes and average daily gain (ADG) in offspring. Fisher’s test, chi-squared test and t test were used for analyzing reproductive rates and production efficiency. No differences (P > 0.05) were found for BW changes, productive efficiency, and pregnancy rate between treatments. Prolificacy was higher (P < 0.05) for primiparous ewes in the OSe group vs the ISe group (66.7 vs 18.2%). No differences (P > 0.05) were found for birth weights of lambs. The ADG was higher (P < 0.05) for the offspring of ISe vs OSe ewes. This indicates that the OSe supplementation improves reproductive parameters, but not the productive such as ADG.